Does the National Level Development Zone foster cities’ innovation capacity? A study from China - Luping Bao (PLoS ONE, 2026)
The article finds that the National Level Development Zone (NLDZ) development has affected urban innovation capacity using panel data from 2014 to 2022 in China. Compared to the West, the East NLDZ of China has a greater effect, and the NLDZ in the Northeast and the Middle Part have the least influence on urban innovation. However, the NLDZ influence of a city at the province level is greater than that at the prefecture level, and the effect of NLDZ on the Bond Area is the greatest, followed by that of the Economic and Technological Development Zone, while the impact of the High-Tech Industrial Development Zone is the least. Finally, we advise preserving a specific quantity of NLDZ to prevent the effect of declining marginal utility.